Tensile properties, barrier properties, and biodegradation in soil of compression-Molded gelatin-dialdehyde starch films - Martucci, Josefa Fabiana (2009)
ABSTRACT: Glycerol (Gly)-plasticized gelatin (Ge) ﬁlms crosslinked with dialdehyde starch (DAS) as environmentally friendly crosslinking agent were successfully produced by compression molding, demonstrating the capacity of gelatin of being transformed into ﬁlms by using thermoplastic processes. The effect of DAS content on the color, light transmission, total soluble matter (TSM), water uptake (WU), water vapor permeability (WVP), oxygen permeability (OP) as well as biodegradability during soil burial was investigated. The addition of up to 10 wt % DAS (Ge-10DAS) generated transparent ﬁlms, with reduced TMS, WU, WVP, and OP values but higher extensivity than the uncrosslinked counterpart. Further incorporating DAS into plasticized-gelatin matrix conducted to phase separation with detrimental effect of transparency and tensile properties. DAS-containing ﬁlms degraded at slow rate than the uncrosslinked counterpart, suggesting that biotic attack during soil burial is restricted by covalent crosslinking points induced by DAS. Ge-10DAS ﬁlms lost about 28% of their initial mass within the ﬁrst 8 days of exposure to degrading medium; therefore, the material can be classiﬁed as rapidly degradable.